Cost of Production for Fresh Market Grapefruit Grown in Indian River, 2020/21: FE1112, 2/2022 - Singerman, Ariel (EDIS, 2022)
This article presents a summary of the costs of production for fresh market grapefruit grown in the Indian River region during 2020/21. The methodology chosen to collect the data consisted of surveying growers directly to closely reflect growers’ costs in the era of HLB. The total cost of production for fresh grapefruit in Indian River during 2020/21 was 2,999.46 per acre. Typical users of the estimates presented herein include growers and consultants, who use them as a benchmark; property appraisers, who use them to compute the taxes for property owners; and researchers, who use the estimates to evaluate the economic feasibility of potential new technologies.